Modeling the management structure for greenhouse gas effects and their impacts on the hydrological cycle in cities - Silva, Sidnei Pereira da; Hanai, Frederico Yuri (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The complexity of cities and the challenges of sustainable planning and management require processes to be treated from a systemic perspective, which, in this study, were carried out using the concept of urban metabolism and modeling of system dynamics. Thus, a model was investigated and proposed to evaluate the effects of Greenhouse Gases (GHG) emissions on climate change and their impacts on the hydrological cycle in a hydrographic basin, addressing economic, social and environmental issues. The structured model makes it possible to visualize the cascade effect of the processes, leading to the observation of the necessary responses, in order to understand their effects, in a systemic, flexible and transparent way. The possibility of creating different scenarios through the dynamic model enables simulations of the present and the future that can be tested to facilitate physical interventions and strategic actions, helping in decision-making processes and in the formulation of public policies in cities.
Keywords: Urban metabolism; system dynamics; climate change; water resources